Białorusini na Uniwersytecie Stefana Batorego w Wilnie : (rekonesans) - Zienkiewicz, Tadeusz (Acta Polono-Ruthenica, 2004)
At Stefan Batory University of Vilnius in the period from 1919 until 1939 apart from Poles also Jews, Byelorussians, Russians and Ukrainians studied. All of them tried to set up their own organizations, to develop cultural and literary activity. Literary life also flourished, issued were poetic volumes, students’ pieces were publisted in all kinds of periodicals; organized were scientific as well as literary-artistic meetings. At the Vilnius University, among others, studied the follasing poets: N. Arsenniewa, A. Bartul, A. Biarozka, Ch. Iliaszewicz as well the literary and historian Stanisław Stankiewicz.